Beat the demon drink. - Phillips, Tom (Nursing standard (Royal College of Nursing (Great Britain) : 1987), 2006)
The article reflects on the important role of nurses in dealing with alcohol dependents in England. It reports that a despairing number of adults are engage in excessive drinking which could result to several health problems. A challenge has been set out to health care agents to find better ways in handling alcohol related cases. New strategies have to be developed such as counseling and disorder identification tests which will greatly help patients' recovery. INSET: What are 'sensible' levels of alcohol consumption?.